2008
DOI: 10.1093/jee/101.3.810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Planting Dates and Insecticide Strategies for Managing Crucifer Flea Beetles (Coleoptera: Chrysomelidae) in Spring-Planted Canola

Abstract: Integration of cultural practices, such as planting date with insecticide-based strategies, was investigated to determine best management strategy for flea beetles (Phyllotreta spp.) (Coleoptera: Chrysomelidae) in canola (Brassica napus L.). We studied the effect of two spring planting dates of B. napus and different insecticide-based management strategies on the feeding injury caused by fleabeetles in North Dakota during 2002-2003. Adult beetle peak emergence usually coincided with the emergence of the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, seeding date influences the extent of flea beetle damage to canola to varying degrees in different regions of the Prairie Ecozone. In North Dakota, United States of America, flea beetle damage to canola was reported to be greater when crops were planted in late April to early May as opposed to those planted in late May (Milbrath et al 1995;Knodel et al 2008). Cárcamo et al (2008) found that canola planted in April in southern Alberta had lower flea beetle populations and less plant damage than crops planted in May, while the opposite occurred in more northern regions of Alberta.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…For example, seeding date influences the extent of flea beetle damage to canola to varying degrees in different regions of the Prairie Ecozone. In North Dakota, United States of America, flea beetle damage to canola was reported to be greater when crops were planted in late April to early May as opposed to those planted in late May (Milbrath et al 1995;Knodel et al 2008). Cárcamo et al (2008) found that canola planted in April in southern Alberta had lower flea beetle populations and less plant damage than crops planted in May, while the opposite occurred in more northern regions of Alberta.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…In general, earlier SOSR planting dates resulted in lower flea beetle abundance in Manitoba, Canada (73) and a reduction in damage in southern Alberta, Canada (36) and in Sweden, even with measurable yield gains (86,87). However, more flea beetles (90) and higher damage were observed with early planting dates in North Dakota (72) and in central and northern Alberta (36). These variable effects have been attributed to different species assemblages among regions, which could result in different responses to environmental conditions that affect flea beetle feeding and plant growth (36,87).…”
Section: Sustainable Control Strategiesmentioning
confidence: 94%
“…Adult flea beetle damage to oilseed rape (OSR) is very fast and difficult to monitor in large fields (120), and there is currently a lack of forecasting models that allow growers to predict economically damaging populations that require treatment (99,113). Therefore, farmers in North America and Europe traditionally used prophylactic applications of in-furrow granules or seed-coated systemic insecticides to control flea beetles in OSR (72,74,85,118,120,134). Since the mid-1990s, nearly all OSR seeds planted in Canada have been treated with systemic neonicotinoid insecticides, which are effective in reducing flea beetle damage to seedlings, usually for up to three weeks (72,113).…”
Section: Management Of Flea Beetlesmentioning
confidence: 99%
See 2 more Smart Citations